Molecular Detection and Genetic Diversity of Casuarina Moth, Lymantria xylina (Lepidoptera: Erebidae). Issue 3 (14th June 2018) - Wang, Rong; Zhang, Zhihan; Hu, Xia; Wu, Songqing; Wang, Jinda; Zhang, Feiping
Abstract: The casuarina moth, Lymantria xylina Swinhoe (Lepidoptera: Erebidae), is an important pest in the Australian pine tree, Casuarina equisetifolia, forest in the coastal area of South China. At the same time, as a closely related species of Lymantria dispar L. (Lepidoptera: Erebidae), it is also a potential quarantine pest. In the present study, specific primers were designed for identification of L. xylina based on the COI barcoding sequence between L. xylina and four other common forest pests. A 569-bp fragment was successfully amplified from 40 L. xylina from five geographical populations in four Chinese provinces. In addition, even through the analysis came from five highly diverse populations of L. xylina, the genetic distances ranged from 0.001 to 0.031. The neighbor-joining tree showed that the species from Hubei and Chongqing were clustered within a distinct group.